Challenging Our Views on ICT, Gender and Education - Cathrine Tømte (Universitetsforlaget, 2011)
The overall picture of the situation relating to gender and Information and Communication Technology (ICT) has so far been that men have been dominating the field and have left the women behind. This has also been the point of departure for policymakers. But, as will be shown in this paper, this male domination of the entire ICT field is not the case anymore. On the contrary, the situation is far more complex. For example, when looking at younger generations, the picture appears to be nuanced; both boys and girls seem to be involved and interested in using different ICT tools, both at school and elsewhere (CERI, 2010). Moreover, along with the new generation, there is the emergence of the new social media, in which girls seem to be highly involved. The present paper explores the ways in which the gender issue appears in youngsters' use of and attitudes towards ICT and how they perform and interact as producers and consumers of digital content.